2017
DOI: 10.1186/s12916-017-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards the concept of disease-modifier in post-stroke or vascular cognitive impairment: a consensus report

Abstract: BackgroundVascular cognitive impairment (VCI) is a complex spectrum encompassing post-stroke cognitive impairment (PSCI) and small vessel disease-related cognitive impairment. Despite the growing health, social, and economic burden of VCI, to date, no specific treatment is available, prompting the introduction of the concept of a disease modifier.Consensus and suggestionsWithin this clinical spectrum, VCI and PSCI remain advancing conditions as neurodegenerative diseases with progression of both vascular and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 111 publications
1
70
0
3
Order By: Relevance
“…It can be inferred that high pulse pressure levels are associated with increased brain white matter lesions and the occurrence of dementia through microvessel disorders in the cerebrum [38][39][40][41][42]. Therefore, those diseases are likely to be synergistic effects to developing dementia [43]. Moreover, one study found the possibility that pulse pressure may be also related to increased cerebrospinal fluid and phosphorylated-tau in normal elderly [44].…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that high pulse pressure levels are associated with increased brain white matter lesions and the occurrence of dementia through microvessel disorders in the cerebrum [38][39][40][41][42]. Therefore, those diseases are likely to be synergistic effects to developing dementia [43]. Moreover, one study found the possibility that pulse pressure may be also related to increased cerebrospinal fluid and phosphorylated-tau in normal elderly [44].…”
Section: Discussionmentioning
confidence: 99%
“…memory impairment, attention trouble, executive dysfunction) are related to several pathological conditions: neurodegenerative diseases (in particular Alzheimer's disease), inflammatory diseases (such multiple sclerosis), neurovascular diseases like stroke, vascular risk factors (hypertension, diabetes, hypercholesterolemia), drugs… These cognitive disorders are developing during several years, with consultation or hospitalization in different medical departments. The clustering tools developed in ClinMine would be able to propose a new stratification of cognitive disorders with the possibility to develop specific therapeutic approach in each cluster [Bordet17]. Secondly, the so-called big data is postulated to offer new opportunity to the resourcing of pathophysiological and therapeutic hypothesis in medicine, by identification of new associations between symptoms, paraclinical parameters, drugs, environmental factors, even though these new hypothesis should have to be confirmed or developed through classical translational and clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TMS findings point out the possibility to predict the progression of mild VCI into VaD, especially in those with concomitant late-onset depression and SIVD (the so-called "vascular depression") [39,50], and to select responders to specific drugs or non-pharmacological treatments [40,41,49,85]. This will be of pivotal importance when designing trials of disease-modifying drugs or approaches based on rTMS or other neuromodulatory interventions [119].…”
Section: Summary Of Findingsmentioning
confidence: 99%